Comparison between primary and secondary mate markets: an analysis of data from lonely hearts columns - Koziel, Slawomir; Pawlowski, Boguslaw (Personality and individual differences, 2003)
Personal advertisements placed in newspapers can be a good source of information on the dynamics of the human mate market. From an analysis of 1587 (776 female and 811 male) advertisements placed in the local Lower Silesian (Poland) newspaper, we were able to compare primary (never married) (PMM) and secondary (divorced/separated) (SMM) mate markets. When controlling for place of residence, it was revealed that the mean time span between the end of education and the age at which females resort to personal advertisement (7–8 years) is very similar in the three education categories. Men who graduated from high school or university were over-represented on the SMM. There were no differences in the residuals of height, weight or BMI between PMM and SMM for females and significant difference only for men's height with relatively taller men on the SMM for the combined two lower levels of education. We also compared PMM and SMM separately for men and women in terms of the rates of offering and seeking resources, attractiveness, commitment and social skills. PMM and SMM differ in three such categories for men and in four for women. However when controlling for advertiser's age, there were only two differences for women (resources were sought for and attractiveness offered more often on the SMM) and one for men (commitment was sought more frequently on the SMM). This indicates that the difference in preferences should be attributed mainly to the age of subjects and only to a smaller extent to the type of mate market (PMM vs SMM).